COVID-19 infection and maternal morbidity in critical care units in Scotland: a national cohort study. (February 2023) - McPeake, J.; Blayney, M.C.; Stewart, N.I.; Kaye, C.T.; Chan Seem, R.; Hall, R.; Martin, C.; Paton, M.; Wise, A.; Puxty, K.; Lone, N.I.; ,
Highlights: Outcomes of women in critical care with COVID-19 are under-reported. Less than 5% of this national cohort had received any form of vaccination. 12% needed an emergency non-obstetric hospital re-admission within 90 days. Abstract: Background: Previous research has shown that, in comparison with non-pregnant women of reproductive age, pregnant women with COVID-19 are more likely to be admitted to critical care, receive invasive ventilation, and die. At present there are limited data in relation to outcomes and healthcare utilisation following hospital discharge of pregnant and recently pregnant women admitted to critical care. Methods: A national cohort study of pregnant and recently pregnant women who were admitted to critical care in Scotland with confirmed or suspected COVID-19. We examined hospital outcomes as well as hospital re-admission rates. Results: Between March 2020 and March 2022, 75 pregnant or recently pregnant women with laboratory-confirmed COVID-19 were admitted to 24 Intensive Care Units across Scotland. Almost two thirds (n=49, 65%) were from the most deprived socio-economic areas. Complete 90-day acute hospital re-admission data were available for 74 (99%) patients. Nine (12%) women required an emergency non-obstetric hospital re-admission within 90 days. Less than 5% of the cohort had received any form of vaccination. Conclusions: This national cohort study has demonstrated that pregnant or recently pregnant women admitted to critical care with COVID-19 were more likely to reside in areas of socio-economic deprivation, and fewer than 5% of the cohort had received any form of vaccination. More targeted public health campaigning across the socio-economic gradient is urgently required.